Osteochondral Autograft Transplantation Technique Augmented by an Ultrapurified Alginate Gel Enhances Osteochondral Repair in a Rabbit Model. Issue 2 (February 2019) - Hishimura, Ryosuke; Onodera, Tomohiro; Hontani, Kazutoshi; Baba, Rikiya; Homan, Kentaro; Matsubara, Shinji; Joutoku, Zenta; Kim, WooYoung; Nonoyama, Takayuki; Kurokawa, Takayuki; Gong, Jian Ping; Iwasaki, Norimasa
Background: One of the most important limitations of osteochondral autograft transplantation (OAT) is the adverse effect on donor sites in the knee. To decrease the number and/or size of osteochondral defects, we devised a method with biomaterial implantation after OAT. Hypothesis: OAT augmented by ultrapurified alginate (UPAL) gel enhances cartilage repair capacity. Study Design: Controlled laboratory study. Methods: Seventy-five osteochondral defects in rabbits were divided into 3 groups: osteochondral defects with OAT alone, defects with OAT augmented by UPAL gel (combined group), and defects without intervention as controls. Macroscopic and histological evaluations of the reparative tissues were performed at 4 and 12 weeks postoperatively. Histological evaluation of graft cartilage degradation was also performed. To evaluate the effects of UPAL gel on graft healing, repaired bone volumes and osseointegration of the graft were evaluated. Collagen orientation and the mechanical properties of the reparative tissue and graft cartilage were also evaluated qualitatively. Results: The macroscopic and histological evaluations of the combined group were significantly superior to the other groups at 12 weeks postoperatively. Regarding degenerative change of the graft, the histological scores of the combined group were significantly higher than those of the OAT-alone group. The values of repaired subchondral bone volumes and osseointegration of the graft were almost identical in both groups. Collagen orientation and the mechanical properties of the reparative tissue and graft cartilage were significantly better in the combined group than in the other groups. Conclusion: Administration of UPAL gel in OAT enhanced cartilage repair and protected graft cartilage without inhibiting subchondral bone repair and graft survival. Clinical Relevance: OAT augmented by UPAL gel decreases the number and/or size of osteochondral grafts, minimizing the risk of donor site morbidity. This combination technique has the potential to improve clinical outcomes and expand the surgical indications for OAT.